How to proceed with asymptomatic modular dual taper hip stems in the case of acetabular revision - Grupp, Thomas Michael; Baxmann, Marc; Jansson, Volkmar; Windhagen, Henning; Heller, Karl-Dieter; Morlock, Michael; Knaebel, Hanns-Peter (Materials, 2020)
How to proceed with a clinically asymptomatic modular Metha® Ti alloy stem with dual taper CoCr neck adapter in case of acetabular revision? To systematically answer this question the status of research and appropriate diagnostic methods in context to clinically symptomatic and asymptomatic dual taper stem-neck couplings has been evaluated based on a systematic literature review. A retrieval analysis of thirteen Metha® modular dual taper CoCr/Ti alloy hip stems has been performed and a rational decision making model as basis for a clinical recommendation was developed. From our observations we propose that in cases of acetabular revision, that for patients with a serum cobalt level of > 4 µg/L and a Co/Cr ratio > 3.6, the revision of the modular dual taper stem may be considered. Prior to acetabular revision surgery a systematic diagnostic evaluation should be executed, using specific tests such as serum metal (Co, Cr) ion analysis, plain antero-posterior and lateral radiographs and cross-sectional imaging modalities (Metal Artefact Reduction Sequence Magnetic Resonance Imaging). For an asymptomatic Metha® dual taper Ti alloy/CoCr stem-neck coupling at the stage of acetabular revision careful clinical decision making according to the proposed model should be followed and overreliance on any single examination should be avoided, considering the complete individual differential diagnosis and patient situation.
Sonstige Körperschaft : Technische Universität Hamburg
Sonstige Körperschaft: Institut für Biomechanik